(untitled) (Journal of Academic Research, 2026)
This study examines the Hadiths regarding the virtues of the Surahs in the exegeses of Al-Hakim al-Jushami and Al-Zamakhshari through an exhaustive, analytical, and critical Hadith study, achieved by surveying, sourcing, and evaluating the Hadiths related to "Al-Sab’ al-Tiwal" (The Seven Long Surahs) both textually and chain-wise, in addition to clarifying their obscure vocabulary, general meaning, and theological employment; it also aims to trace the scholarly relationship and Al-Zamakhshari’s intellectual debt to Al-Jushami, concluding that weak and fabricated Hadiths predominate in this domain, while demonstrating the extent of both scholars’ theological orientation in selecting these Hadiths.